Pengaruh Penggunaan Kitosan Dengan Berat Molekul Yang Berbeda Terhadap Ekspresi Tumor Necrosis Factor Alpha (Tnf Α) Pada Penyembuhan Luka Pencabutan Gigi Tikus Rattus Norvegicus - Sularsih Sularsih; Soeprijanto Soeprijanto (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Chitosan which is composed glucosamine and acetlyglucosamine has been proven to be biologically, renewable,biodegradable, biocompatible and biofunctional. Tumor necrosis factor alpha (TNF a) is inflammatory factors that have important role in wound healing process of dental extraction. The aim of this study was to compare the expression of Tumor Necroting Factor Alpha (TNF a) on wound healing process of dental extraction using different molecular weight of chitosan gel. Rattus nornegicus strain wistar male, aged 8-16 weeks, divided into 3 treatment groups namely group 1 which given chitosan gel with high molecular weight. Group II which given chitosan with low molecular weight and group III which given’t chitosan gel. Chitosan gel were applied into the socket of dental extraction. Rat was decaputated 3 and 4 days after chitosan application and the jaw in the treated regions and control group were cut for imunohistochemical examination to observe the expression of Tumor Necroting Factor Alpha (TNF a). Data were analyzed using One way Anova test. The result showed significant differences of expression of Tumor Necroting Factor Alpha (TNF a) between groups with different molecular weight (p<0,05). The expression of TNF using chitosan with high and low molecular weight were 11,83±2,137 and 9,60±0,894 on 3 days examination and 17,00±1,871 and 12,17±1,722 on 4 days examination. The application of Chitosan gel with high molecular weight on wound healing process of dental extraction could stimulate the expression of TNF a.